Understanding the Impact of Future Social Self-Concepts on Newcomer Adjustment - Jonas Franz Buerkner (Junior Management Science (JUMS), 2022)
The purpose of this study is to investigate the impacts of future social self-concepts on newcomer short-term adjustment. Employing a qualitative longitudinal design based on interviews, this work aims to uncover how the shape of identities before and three weeks after entry, as well as the identity processes between them, impact adjustment success. This is important because adjustment is a precursor for job outcomes, such as performance, satisfaction, and intentions to remain. In the first part, the relevance of identities for job outcomes is carved out and major theoretical contributions to identity and socialization are identified and presented. The thesis then discusses a fitting methodology for studying identity and describes key methodological choices. Three newcomers participated in the narrative-based interviews. The first interview was conducted shortly before the second interview three weeks after organizational entry. The interviews were audio-recorded, transcribed, and coded employing an abductive coding procedure. The results support the view that identity plays a key role in newcomer socialization and illustrate currently discussed identity processes. The complexity of self-concept phenomena involved in newcomer socialization calls for further research efforts.
Keywords: 650; Newcomer socialization; Newcomer adjustment; Self-concept; Possible selves; Identity partnership